Power Quality in Microgrids including Supraharmonics: Issues, Standards, and Mitigations - Alkahtani A.A.; Alfalahi S.T.Y.; Athamneh A.A.; Al-Shetwi A.Q.; Mansor M.B.; Hannan M.A.; Agelidis V.G. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric power transmission networks; Microgrids; Power quality; Renewable energy resources; Small power plants; Smart power grids; Distributed generators; Distribution power systems; Energy management softwares; Mitigation strategy; Renewable energy source; Standards development; Technological advancement; Voltage and current harmonics; Electric power system control